The Relationship between Physical Education Teachers' Benefits of Participation in Recreational Activities, Leisure Time Satisfaction Levels, and Cognitive Flexibility - Özlem Sinem Uslu; Alpaslan Gorucu (Selcuk University, 2024)
The purpose of this study was to examine the relationship between physical education teachers' recreational activity participation, leisure time satisfaction, and cognitive flexibility. The relationship between the benefits that physical education teachers derive from participating in recreational activities, their levels of satisfaction during leisure time, and their cognitive flexibility. A total of 515 participants took part in the research. Out of these, 191 were female and 324 were male. All the participants were employed by physical education departments in Antalya. The teachers who participated in the research were selected using the homogeneous sampling method, which is one of the purposeful sampling methods, and voluntary participation was considered in determining the participants. In the collection of research data, the scales were filled in electronically. The Personal Information Form developed by the researcher was used to obtain sociodemographic data. In addition, the Recreation Utility Scale designed by Ho in 2008 (26), the Leisure Time Satisfaction Scale developed by Beard and Ragheb in 1980 (6), and the Cognitive Flexibility Scale developed by Martin and Rubin in 1995 (34) were used to measure how individuals spend their 'leisure time' physically, psychologically, and socially. The data obtained from the scales were analyzed and interpreted through statistical methods based on the research problems. SPSS version 25 statistical programs was used for data analysis. Descriptive statistical analyses, including frequency and percentage distributions of the responses to the scale questions, as well as arithmetic mean and standard deviation scores, interpretive statistical analyses were performed based on the results of the normality analysis of the data, and correlation (Pearson) analysis was used to determine the relationships between variables. The reliability level for this study was accepted as 0.05. When the findings were examined, according to the results of the research, it can be said that the physical education teachers participating in the research generally think that recreational activities are beneficial in terms of physical, psychological, and social aspects. However, they exhibited an attitude that recreational activities contribute more to individuals' physical and psychological characteristics while contributing less to their social lives or socialization. Additionally, it can be said that they are generally satisfied with leisure activities, but they believe that the places where these activities are carried out need to be better designed or increased. The cognitive flexibility levels of physical education teachers were found to be close to "somewhat agree" and they have a positive cognitive flexibility. According to the findings obtained regarding the sub-problem of the research, "Is there a statistically significant relationship between the benefits of physical education teachers' participation in recreational activities, their leisure satisfaction, and cognitive flexibility levels?", it was determined that there were statistically significant (p